Cerebral blood flow changes induced by high-frequency repetitive transcranial magnetic stimulation combined with cognitive training in Alzheimer's disease - Qin, Yuanyuan; Ba, Li; Zhang, Fengxia; Jian, Si; Zhang, Min; Zhu, Wenzhen (Frontiers in Neurology, 2023)
Background and purpose Hypoperfusion of the posterior cingulate cortex (PCC) and precuneus has consistently been reported in patients with Alzheimer's disease (AD). Repetitive transcranial magnetic stimulation (rTMS) combined with cognitive training (COG) is effective in alleviating the symptoms of patients with mild AD. This study investigated the effects of rTMS-COG therapy on cerebral blood flow (CBF), with a special interest in the PCC/precuneus, and whether observed CBF changes are associated with changes in neuropsychological assessments in AD. Materials and methods Twenty-one patients with mild or moderate AD were randomly divided into real rTMS (n = 11) and sham treatment (n = 10) groups, both combined with COG. Neuro-navigated 10 Hz rTMS was used to stimulate the left dorsolateral prefrontal cortex (DLPFC) and then the left lateral temporal lobe (LTL) for 20 min each day for 4 weeks in the real rTMS group. All patients with AD underwent neuropsychological assessment, pseudo-continuous arterial spin labeling, and structural 3D T1-weighted MRI before treatment (T0), immediately after treatment (T1), and 4 weeks after treatment (T2). CBF in the precuneus, PCC, and stimulation targets at the region-of-interest (ROI) level, as well as whole-brain CBF changes at the voxel level, were compared between the two groups at three timepoints. Results rTMS-COG therapy revealed significant group × time interactions for the Mini-Mental State Examination (F = 5.339, p = 0.023, η2 = 0.433) and activities of daily living (F = 5.409, p = 0.039, η2 = 0.436) scores. The regional CBF in the precuneus showed a significant group × time interaction (F = 5.833, p = 0.027, η2 = 0.593). For voxel-level analysis, a significant group main effect was found in the left limbic lobe cluster, with the maximal peak in the left parahippocampus (p < 0.001, uncorrected, peak at [−16 −8 −24]). Simple effects analysis indicated that rTMS-COG therapy induced a decrease in CBF in the precuneus at T1 (p = 0.007) and an increase in the left parahippocampus at T2 (p=0.008). CBF decrease in the precuneus was correlated with better cognitive function immediately after treatment (T1) (r =−0.732, p=0.025). Conclusion Neuropsychological assessments showed immediate and long-term effects on cognitive function and activities of daily living after rTMS-COG therapy. CBF changes induced by high-frequency rTMS-COG therapy are region-dependent, showing immediate effects in the precuneus and long-term effects in the left parahippocampus. These results provide imaging evidence to understand the underlying neurobiological mechanism for the application of rTMS-COG in AD.